Factors Influencing Oil Palm Plantation Companies’ Disclosure of Biological Assets - Tio Sandela Nugroho; Kunti Sunaryo (AIBPM Publisher, 2025)
Complete regulations regarding biological assets are contained in the PSAK 69 Statement which adopts the provisions of IAS 41. This research aims to provide empirical evidence regarding the influence of biological asset intensity, growth, public ownership, type of public accounting firm (KAP), and internationalization level on biological asset disclosure. The population in this study were oil palm plantation companies listed on the Indonesia Stock Exchange (IDX) in the period 2018 to 2022. The sample was selected using a purposive sampling method, and from the specified criteria, 14 companies were selected with a total of 70 observation data. This research is a quantitative study using secondary data, which is then analyzed using the multiple regression method. The research results show that the intensity of biological assets has a positive effect, while the level of internationalization has a negative effect on the disclosure of biological assets in oil palm plantation companies listed on the IDX in 2018-2022. However, the variables of company growth, public ownership, and type of KAP had no effect on the disclosure of biological assets in oil palm plantation companies in that period. This research implies that oil palm plantation companies with higher biological asset intensity are more likely to disclose biological assets, while internationalization negatively impacts such disclosure practices.